Immigration, remittances, and business cycles - Federico S. Mandelman; Andrei Zlate (Federal Reserve Bank of Atlanta, 2012)
Using data on border enforcement and macroeconomic indicators from the United States and Mexico, we estimate a two-country business cycle model of labor migration and remittances. The model matches the cyclical dynamics of unskilled migration and documents the insurance role of remittances in consumption smoothing. Over the cycle, immigration increases with the expected stream of future wage gains, but it is dampened by a sunk emigration cost. Migration barriers slow the adjustment of the stock of immigrant labor, enhancing the volatility of unskilled wages and remittances. Changes in border enforcement have asymmetric welfare implications for the skilled and unskilled households.
Keywords: F22; F41; 330; labor migration; sunk emigration cost; skill heterogeneity; international business cycles; Bayesian estimation; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Makroökonomischer Einfluss; Konjunkturzusammenhang; Real Business Cycle; Sunk Costs; Dynamisches Gleichgewicht; Theorie; Schätzung; USA; Mexiko